2019
DOI: 10.3389/fgene.2019.00528
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Tacrolimus Pharmacokinetics Identifies Novel Single Nucleotide Polymorphisms in the Convalescence and Stabilization Periods of Post-transplant Liver Function

Abstract: After liver transplantation, the liver function of a patient is gradually restored over a period of time that can be divided into a convalescence period (CP) and a stabilizing period (SP). The plasma concentration of tacrolimus, an immunosuppressant commonly used to prevent organ rejection, varies as a result of variations in its metabolism. The effects of genetic and clinical factors on the plasma concentration of tacrolimus appear to differ in the CP and SP. To establish a model explaining the variation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Multivariate linear regression analysis was used to screen the influence factors of tacrolimus pharmacokinetics. The incorporated cofactors included daily drug dose, serum albumin concentration, hemoglobin, glutamate pyruvate transaminase, and total bilirubin; all reported to have the potential effects on tacrolimus pharmacokinetics [ 6 , 8 ], as well as FIS genotype classification and recipient SLCO1B1 rs2291075. The results (Table 1 ) have shown that daily dose, FIS genotype classification, and total bilirubin were the consistent predictors for tacrolimus elimination in convalescence period and stabilizing period after liver transplantation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multivariate linear regression analysis was used to screen the influence factors of tacrolimus pharmacokinetics. The incorporated cofactors included daily drug dose, serum albumin concentration, hemoglobin, glutamate pyruvate transaminase, and total bilirubin; all reported to have the potential effects on tacrolimus pharmacokinetics [ 6 , 8 ], as well as FIS genotype classification and recipient SLCO1B1 rs2291075. The results (Table 1 ) have shown that daily dose, FIS genotype classification, and total bilirubin were the consistent predictors for tacrolimus elimination in convalescence period and stabilizing period after liver transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…The CYP3A5 protein expression quantity was reduced obviously in donor liver and recipient intestine in convalescence phase, which resulted in high tacrolimus C/D ratios. And the CYP3A5 protein produced by donor liver and recipient intestine cells returned to nearly normal levels in stationary phase [ 6 ]. The quantity of functional CYP3A5 was very low in SE subgroup liver transplantation patients due to donor and recipient CYP3A5 rs776746 polymorphisms which produced in CYP3A5 protein without enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was discovered in Japan and isolated in 1984 by researchers of Fujisawa Pharmaceutical Co., during a selection of immunosuppressive activity in compounds isolated from fermentation broths using the bacteria Streptomyces tsukubaensis (Nakamura, 2019). In 1987, the first description of this immunosuppressant was published, and it was intended for the treatment of transplants (Kino et al, 1987;Liu et al, 2019). It was found that this drug is also indicated in other clinical cases such as in the treatment of dermatological disorders, atopic dermatitis (Dähnhardt, Bastian, Dähnhardt-Pfeiffer, Buchner, & Fölster-Holst, 2019), and ophthalmic diseases such as conjunctivitis (Erdinest, Ben-Eli, & Solomon, 2019).…”
Section: Introductionmentioning
confidence: 99%